Design of machine element in alpha type stirling machine innovation design based on plastic waste. Issue 1 (December 2020) - Satria, Dhimas; Rosyadi, Imron; Lusiani, Rina; Listijorini, Erny
Abstract: One effort to overcome the use of fossil fuels is to use alternative energy sources, including plastic waste. Stirling engine is an external combustion engine that can utilize heat from various heat sources. In this research, an analysis of the design of the engine elements in the alpha-type Stirling engine design innovation is based on plastic waste, so it is expected to get the best and safest engine element design specifications. Based on the analysis results of calculations based on the Kwurmi method, it has been obtained the specifications of the design results of the engine elements are as follows: shaft design (length = 250 mm, diameter = 15 mm), post design ( length = 20 mm, width = 6 mm, thickness = 6 mm), pulley design (driver diameter = 100 mm, diameter driven = 60 mm), belt design (length = 987 mm, width = 30 mm, thickness = 5 mm), Stirling engine (power = 94.3 to 205.4 watts, engine speed = 300 to 1305 rpm, heat temperature = 623 ° k, cold temperature = 305 ° k, phase angle = 180 °, dimension = 580 mm × 250 mm × 700 mm, thermal efficiency = 0.51).